The competitiveness of Brazilian tourist destinations - Barbosa, Luiz Gustavo Medeiros (2013)
This thesis proposes a construct to measure the competitiveness of Brazilian tourist destinations and orient the actions of public and private tourism managers. The model of this study is based on a relevant literature review, a panel with specialists that have expertise in Brazilian tourism and field research. The investigation was carried out in 15 Brazilian tourist cities, representative of the socioeconomic diversity that characterises the heterogeneity of a developing country. The results of the study show the level of competitiveness of these 15 destinations according to the 13 dimensions proposed in the model, identifying the strong and weak points of local tourism. An assessment was carried out in detail that should serve to assist public managers in the strategic planning of these cities now and in the future. As a complementary result, the study may be successfully replicated in other destinations, thus initiating a historical series for monitoring the competitiveness of Brazilian tourist destinations.